JSW Steel's Ispat acquisition (B) : the setback - Sharma, Sunil, (SAGE Knowledge. Cases., 2016)
JSW Steel has made the decision to acquire rival company Ispat. However, upon doing so, they are saddled with Isapt's poor financial performance, supply chain issues, and financial debts. Now JSW must figure out how to proceed with Ispat: spend the time and resources to fix its issues, or cut the company loose to relieve themselves of the burden.